Democracy and Stock Market Performance in African Countries - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Purpose This paper assesses the incidence of political institutions on stock market performance dynamics in Africa. Design/methodology/approach The estimation technique used is a Two-Stage-Least Squares Instrumental Variable methodology. Channels of democracy, polity and autocracy are instrumented with legal-origins, religious-legacies, income-levels and press-freedom qualities to account for stock market performance dynamics of capitalization, value traded, turnover and number of listed companies. To ensure robustness of the analysis, the following checks are carried out: (1) usage of alternative indicators of political institutions; (2) employment of two distinct interchangeable sets of moment conditions that engender every category of the instruments; (3) usage of alternative indicators of stock market performance; (4) account for the concern of endogeneity; (5) usage of Principal Component Analysis(PCA) to reduce the dimensions of stock market dynamics and political indicators and then check for further robustness of findings in the regressions from resulting indexes. Findings Findings broadly demonstrate that democracy improves investigated stock market performance dynamics. Practical implications As a policy recommendation, the role of sound political institutions is crucial for financial development in Africa. Democracies have important effects on both the degree of competition for public office and the quality of public offices that favor stock market development in the African continent. Originality/value To the best of our knowledge this is the first paper to assess the incidence of democracy on stock market performance in an exclusive African context. Political strife has plagued many African countries and continue to pose a significant threat to financial market development.
Keywords: G10; G18; G28; P16; P43; 330; Financial Markets; Government Policy; Political Economy; Development